2021
DOI: 10.3390/children8040314
|View full text |Cite
|
Sign up to set email alerts
|

Boredom in Adolescence: Validation of the Italian Version of the Multidimensional State Boredom Scale (MSBS) in Adolescents

Abstract: Boredom in adolescence is often underestimated, although it may be the sign of a profound unease or be associated with psychological disorders. Given the complexity of the construct of boredom and its increasing prevalence among adolescents in recent years, the present study aimed to validate the factorial structure of the Italian version of the Multidimensional State Boredom Scale (MSBS) in adolescents using a cross-validation approach. The study involved 272 students (33.8% males, 66.2% females) aged 14–19 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…As a matter of fact, the main criticism that the MSBS has received is its length (Fahlam & al., 2013). Outside the original version, the Cameroonian version stands out with better fit indices than the Italian adaptation of (Spoto et al, 2021) Moreover, the study of the correlates showed that the Cameroonian version, like the previous adaptations, can explain the realities related to boredom. This result provides further evidence to the validity of this construct.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As a matter of fact, the main criticism that the MSBS has received is its length (Fahlam & al., 2013). Outside the original version, the Cameroonian version stands out with better fit indices than the Italian adaptation of (Spoto et al, 2021) Moreover, the study of the correlates showed that the Cameroonian version, like the previous adaptations, can explain the realities related to boredom. This result provides further evidence to the validity of this construct.…”
Section: Discussionmentioning
confidence: 90%
“…This research will also enable us to continue the validation work of this instrument in different contexts undertaken since 2012. Unlike Farmer and Sundberg's (1986) boredom predisposition tool, which has been proven to be robust in different cultural contexts, cross-cultural validation studies of the MSBS are rather recent and need to be intensified (Liu Yong et al, 2013;Alda et al, 2015;Spoto et al, 2021).…”
Section: What Is the Need For A Translation And Adaptation Of The Msb...mentioning
confidence: 99%
“…The internal consistency was good, with Cronbach's alphas ranging from .80 to .92 for the subscales and of .95 for the overall boredom factor (Fahlman et al, 2013). This questionnaire was adapted for adolescents (Spoto et al, 2021) and translated into Spanish (Alda et al, 2015), among other changes.…”
Section: State Boredommentioning
confidence: 99%
“…Furthermore, new domain-specific scales have been developed, such as the Bored of Sports Scale (BOSS; Wolff, Bieleke, Stähler, et al, 2021), which is to be used in a sporting context. Finally, in recent years, many validations of translated versions of these scales (e.g., Peng et al, 2020), as well as adapted versions (e.g., Spoto et al, 2021), have been published. In the paragraphs below, we review these recent developments.…”
mentioning
confidence: 99%
“…Faísca et al [ 17 ], Gomes et al [ 18 ], Pechorro et al [ 19 ], and Spoto et al [ 20 ] provide the results of their research on the validation and adaptation of instruments (Lab-TAB, Quiet Time Program, SUPPS-P Impulsive Behavior Scale, and the Multidimensional State Boredom Scale, respectively), which have practical implications in the assessments and interventions involving children and adolescents.…”
mentioning
confidence: 99%